2010
DOI: 10.1128/ec.00282-09
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes Are Depleted at the VSG Expression Site Transcribed by RNA Polymerase I in African Trypanosomes

Abstract: In most eukaryotes, RNA polymerase I (Pol I) exclusively transcribes long arrays of identical rRNA genes (ribosomal DNA [rDNA]). African trypanosomes have the unique property of using Pol I to also transcribe the variant surface glycoprotein VSG genes. VSGs are important virulence factors because their switching allows trypanosomes to escape the host immune system, a mechanism known as antigenic variation. Only one VSG is transcribed at a time from one of 15 bloodstream-form expression sites (BESs). Although i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 34 publications
(37 reference statements)
12
101
0
Order By: Relevance
“…The active BES differs from silent BESs in that it is actively transcribed by RNA polymerase I [59]. In addition, the active BES forms an open chromatin structure depleted of most nucleosomes, while silent BESs are packed with nucleosomes [60,61]. Our data suggest that the transcriptional status and/or the chromatin structure of the DSB site may influence the choice of DSB repair mechanism.…”
Section: Tbrad51-dependent Hr-mediated Dna Damage Repair and Vsg Switmentioning
confidence: 83%
“…The active BES differs from silent BESs in that it is actively transcribed by RNA polymerase I [59]. In addition, the active BES forms an open chromatin structure depleted of most nucleosomes, while silent BESs are packed with nucleosomes [60,61]. Our data suggest that the transcriptional status and/or the chromatin structure of the DSB site may influence the choice of DSB repair mechanism.…”
Section: Tbrad51-dependent Hr-mediated Dna Damage Repair and Vsg Switmentioning
confidence: 83%
“…The mechanism controlling the selective activity of a single ES at a time is still unknown, although several factors have been found to be involved, such as differential chromatin/histone acetylation and methylation between active and inactive ESs (6-8); nucleosome depletion in the active ES (9,10); and the influence of various negative transcription modulators such as a histone methylase, a high-mobility group protein, histone H1, NLP (a nucleoplasm-like protein), a FACT subunit (a chromatin remodeler), a SWI/SNF (a chromatin remodeling factor), ORC1 and MCM-BP (proteins involved in the initiation of DNA replication), RAP1 (a telomere-binding protein), histone chaperones, or a lamin-like protein (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, no master ES regulator has been identified so far.…”
mentioning
confidence: 99%
“…In the case of the ESs, it has recently been shown that the active ES in bloodstream-form T. brucei is depleted of nucleosomes (13,51), indicating that chromatin remodeling plays a key role in ES activation. This is supported by the discovery that a number of proteins involved in epigenetic control play a role in ES regulation, including the T. brucei imitation switch homologue TbISWI (21), the telomere-binding protein RAP1 (64), and the histone methyltransferase DOT1B (14).…”
mentioning
confidence: 99%